Opozycja wewnątrzpartyjna w Socjaldemokratycznej Partii Niemiec w latach 1980-1982 - Świder, Małgorzata (Polityka i Społeczeństwo, 2020)
At the beginning of the 1980s a very serious internal conflict within the Social Democratic Party of Germany (SPD) appeared, which was played out on a few levels. The first one was the personal level, the second one was the program and ideology level. Both levels, especially in 1981 and in 1982 started to penetrate the strengthening the conflict and the signs of intra-party breakup, and revealing the views and actions of SPD party members, being in open opposition to the official policy of the social liberal government and the social democratic chancellor. Having entered opposition, the party adjusted the party program from above to the expectations of its members and its electorate, taking over a part of the intra-party opposition program (of the so-called left-wing of the party).